Reflective Practices to Study Group Dynamics: Implement Empowerment and Understand the Functioning of Groups - Rania, Nadia; Coppola, Ilaria; Pinna, Laura (Frontiers in Psychology, 2021)
Introduction. Individual and group reflection practices are qualitative methods useful in a group context to develop group skills and more awareness of the dynamics that take place within the group to which one belongs. Aim. The aim of this work is to highlight how individual reflective practices and group reflections contribute to the development of group skills. More specifically, the effectiveness of relevant group dynamics is investigated, with the aim of creating a space for reflection, and activation for individual and group empowerment. Participants. The participants were 130 university students (86% female), resided in northwestern Italy, and had a mean age of 27.5 years (SD = 7.52). They were randomly divided into 23 groups (ranged from four to nine members). Method. The participants engaged in several online training activities and at the end of every activity they completed individual reflection practice in which they presented both positive and negative aspects related to the group experiences. Then they participated in online group reflections that allowed them to reflect on the group dynamics, particular attention given to factors such as climate, participation and roles played by each participant in a variety of training activities. This study analyzes 130 individual reflective practices and 23 group reflections. The data collected through individual reflective practices and the transcripts of the group reflections were analyzed using grounded theory. Two independent judges analyzed and categorized the data and then identified the main common categories that emerged by the support of Nvivo software. Results. From the analysis of the content, it is determined that the participants, based on the construction of the individual and group reflections, paid greater attention to the dynamics that occurred within the group during the various activities in which they participated, thus allowing them to be more aware of the various factors that affected the importance attributed to the different roles, the climate, and their active participation. Conclusion. Combined, these factors allowed participants to strengthen their relationships with each other and enhance the cohesion of the group.